2012
DOI: 10.1063/1.3698204
|View full text |Cite
|
Sign up to set email alerts
|

Cantilever deflection associated with hybridization of monomolecular DNA film

Abstract: Recent experiments show that specific binding between a ligand and surface immobilized receptor, such as hybridization of single stranded DNA immobilized on a microcantilever surface, leads to cantilever deflection. The binding-induced deflection may be used as a method for detection of biomolecules, such as pathogens and biohazards. Mechanical deformation induced due to hybridization of surface-immobilized DNA strands is a commonly used system to demonstrate the efficacy of microcantilever sensors. To underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…34 Previous theoretical works reveal that small amounts of disorder in the DNA monolayer can affect cantilever deflection. 28,[42][43][44] Moreover, Kosaka et al 19 , proved the heterogeneity of highly packed DNA monolayers on gold obtained by selfassembly. We speculate that the observed variations in the value of ΔS from sample to sample, for the same sequence and incubation conditions, could arise due to slight probe density differences or inhomogeneities.…”
Section: Resultsmentioning
confidence: 99%
“…34 Previous theoretical works reveal that small amounts of disorder in the DNA monolayer can affect cantilever deflection. 28,[42][43][44] Moreover, Kosaka et al 19 , proved the heterogeneity of highly packed DNA monolayers on gold obtained by selfassembly. We speculate that the observed variations in the value of ΔS from sample to sample, for the same sequence and incubation conditions, could arise due to slight probe density differences or inhomogeneities.…”
Section: Resultsmentioning
confidence: 99%
“…Different research disciplines can be identified in the rapidly developing field of DNA nanotechnology, Figure . These include application of the unique recognition properties of nucleic acids or aptamers as recognition ligands for sensing events and implementation of catalytic nucleic acids as amplifying labels for sensing processes. Indeed, numerous studies have addressed the use of nucleic acids in developing electrochemical, electronic, optical, microgravimetric, and mechanical sensors, and different methods to amplify the readout signals and to increase the sensitivity of the sensing platforms by catalytic labels , or target regeneration , schemes were demonstrated. A further discipline in DNA nanotechnology involves controlled self-assembly of DNA subunits into one-dimensional (1D) templates, two-dimensional (2D) lattices, and three-dimensional (3D) nanostructures. Ingenious DNA subunits (tiles) consisting of pretailored hybridization arms or nucleic acid chains exhibiting geometrical complementarity were used to assemble programmed DNA nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Deformities in polymeric films after the incorporation of biomolecules can vary based on the specific techniques and materials used. Research has shown that polymer films can exhibit significant changes in physical and mechanical properties when doped with biological molecules [31]. For example, the adsorption of proteins such as fibronectin can be influenced by the type of dopant used, affecting the binding to proteins on the film surface [32].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%